Analysis Of Knowledge In Choosing Delivery Aid For Mothers In The Region Work Of Biromaru District Health Center Sigi Central Sulawesi Province - Furnamasari, Dyan; Candra Wahyuni (Universitas STRADA Indonesia, 2017)
According to the 2015 ministry of health of the republic of Indonesia data, the proportion of deliveries in health care facilities in Indonesia was 79%. This shows that the proportion of deliveries in non-health workers is still high. While in Central Sulawesi province, the proportion of deliveries in health care facilities is approximately 30%. The results of a preliminary study conducted by researchers in Loru Village, Biromaru Health Center Working Area, Sigi Regency, Central Sulawesi Province by interviewing 10 pregnant women, it was found that 5 (50%) pregnant women did not know about the signs and dangers of labor. The statement of one of the mothers was that there was a lack of knowledge in choosing the right birth attendant. This causes the behavior of mothers and family members to carry out pregnancy checks with midwives. The purpose of this study was to analyze the relationship between Knowledge and the Selection of Birth Assistance in mothers in Loru Village, Biromaru Health Center Working Area, Sigi Regency, Central Sulawesi Province. The design of this study was correlational analytic with a cross-sectional approach. The number of samples in this study was 37 respondents. Then for sampling using the Accidental Sampling technique. The data collection instrument used a questionnaire and data analysis used the Chi square test. The results of the study showed that most respondents had good knowledge about childbirth, which was 54.1%, in addition, most respondents chose to be assisted by health workers in giving birth, which was 83.8%. The results of the chi square test showed a relationship between knowledge and the selection of assistants with a P Value of 0.012 <α = 0.05. There is a Relationship between Knowledge and the Selection of Childbirth Assistants in Mothers in Loru Village, Biromaru Health Center Work Area, Sigi Regency, Central Sulawesi Province